The spectrum of movement disorders in children with anti‐NMDA receptor encephalitis. Issue 4 (11th February 2013) - Baizabal‐Carvallo, José Fidel; Stocco, Amber; Muscal, Eyal; Jankovic, Joseph
ABSTRACT Background Movement disorders are frequent but difficult to characterize in patients with anti‐N‐methyl‐d‐aspartate receptor (NMDAR) encephalitis. Methods The phenomenology of movement disorders was characterized after a detailed examination of children with anti‐NMDAR‐encephalitis. Results We studied 9 children (5 females), ages 3–14 years, with confirmed anti‐NMDAR‐encephalitis. All patients presented with at least 1 movement disorder, including chorea (n=4), stereotypic movements (n=4), ataxia (n=3), limb dystonia (n=2), limb myorhythmia (n=2), oromandibular dystonia (n=2), facial myorhythmia, blepharospasm, opisthotonus, athetosis, and tremor (n=1, each). More than a single movement disorder was observed in 6 of these patients. Resolution of the abnormal movements was observed in all patients with immunotherapy; 1 patient improved with tetrabenazine. Conclusions A wide variety of movement disorders, often in combination, can be observed in children with anti‐NMDAR encephalitis. Patients commonly present with more than a single movement disorder. © 2013 Movement Disorder Society